2016
DOI: 10.1016/j.bpsc.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Attention-Deficit/Hyperactivity Disorder Symptoms Coincide With Altered Striatal Connectivity

Abstract: Background Cortico-striatal network dysfunction in attention-deficit/hyperactivity disorder (ADHD) is generally investigated by comparing functional connectivity of the main striatal sub-regions (i.e., putamen, caudate, and nucleus accumbens) between an ADHD and a control group. However, dimensional analyses based on continuous symptom measures might help to parse the high phenotypic heterogeneity in ADHD. Here, we focus on functional segregation of regions in the striatum and investigate cortico-striatal netw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
37
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 72 publications
11
37
0
6
Order By: Relevance
“…Using 3.0 Tesla fMRI scanner, and estimating the Korean ADHD Rating Scale, the Wisconsin Card Sorting Test, the 7-and 14-ring drill test with hop jumps, it found that childhood ADHD patients expressed an extended distance-traveled estimate and a decreased-speed on the 14-ring hop jump task whereas on the Wisconsin Card Sorting Test task, ADHD children demonstrated decreased activation within right gyrus brain region with total distance on the 14-ring hop jump task was negatively correlated with the mean β value of Cluster 2 in ADHD children according to the Korean ADHD Rating Scale (Kang et al, 2016) [12]. Despite these indications, using task-based fMRI to assess functional connectivity alterations between key reward processing regions in adolescents and young adults presenting ADHD [13], it appears some manner of 'developmental normalization' occurred or that the reward-processing deficits earlier observed emanated from particular functional connectivity alterations in general task-related networks.…”
mentioning
confidence: 99%
“…Using 3.0 Tesla fMRI scanner, and estimating the Korean ADHD Rating Scale, the Wisconsin Card Sorting Test, the 7-and 14-ring drill test with hop jumps, it found that childhood ADHD patients expressed an extended distance-traveled estimate and a decreased-speed on the 14-ring hop jump task whereas on the Wisconsin Card Sorting Test task, ADHD children demonstrated decreased activation within right gyrus brain region with total distance on the 14-ring hop jump task was negatively correlated with the mean β value of Cluster 2 in ADHD children according to the Korean ADHD Rating Scale (Kang et al, 2016) [12]. Despite these indications, using task-based fMRI to assess functional connectivity alterations between key reward processing regions in adolescents and young adults presenting ADHD [13], it appears some manner of 'developmental normalization' occurred or that the reward-processing deficits earlier observed emanated from particular functional connectivity alterations in general task-related networks.…”
mentioning
confidence: 99%
“…Os limiares de z foram ajustados para melhor apresentação gráfica dos mapas, lembrando que em todos os voxels 2,5 > z > 2,5. Assim como este estudo, alguns estudos prévios também falharam em encontrar diferenças categóricas na conectividade do NAcc e da amígdala, mas encontraram correlações interessantes entre conectividade e comportamento (64,67,69). Alguns aspectos podem justificar a ausência de resultados positivos para a maioria das nossas análises categóricas.…”
Section: Associação Entre Conectividade Do Nacc E Comportamentounclassified
“…Terceiro, ainda devido à estratégia de recrutamento, a amostra deste estudo pode ser mais heterogênea do que a de outros estudos e, consequentemente, o tamanho amostral dos grupos com transtornos pode não ter sido suficiente para a detecção de diferenças de menor magnitude. A estratégia dimensional usada neste e em estudos anteriores (13,64,67,69) contrabalanceia a limitação da heterogeneidade ao avaliar correlatos neurobiológicos dos TCD e do TDAH e possibilita a investigação de correlatos neurais de comportamentos associados aos transtornos e que cruzam as categorias diagnósticas. Quarto, por ser uma amostra selecionada da comunidade, muito poucos participantes estavam fazendo uso de medicações psicotrópicas, logo é improvável que efeitos de uso de medicações por longo prazo influenciaram os resultados.…”
Section: Associação Entre Conectividadeunclassified
See 2 more Smart Citations